Factors Influencing Strategic Technology Alliance Formation of Malaysian Manufacturers - Juhaini, Jabar; Soosay, Claudine; Othman, Norfaridatul Akmaliah; Tahir, Md. Nor Hayati (International Association of Computer Science & Information Technology Press, 2011)
This paper examines the relationship between organisations’ resource availability and absorptive capacity as well as type of alliances with organisational performance. The results are based on survey data from 335 manufacturing organisations in Malaysia that were then analysed using Structural Equation Modelling (SEM). The result establishes that Malaysian manufacturers need to increase their efforts in increasing internal resources that are the source of competitive advantage in order to achieve superior manufacturing performance.